1986
DOI: 10.1159/000167332
|View full text |Cite
|
Sign up to set email alerts
|

Renal Hemodynamic Effects of Tertatolol in Essential Hypertension

Abstract: Tertatolol, a new β-blocker, and propranolol, considered a reference β-blocker, were given orally (5 and 160 mg slow release, respectively) for 15 days to two groups of patients with essential hypertension in order to compare their effects on renal hemodynamics. Systolic and diastolic blood pressure, heart rate, and erect plasma renin activity fell significantly in both groups while prostaglandin E2 urinary excretion was unchanged. Tertatolol administration produced increases in glomerular filtratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Indeed, a renal function impair ment is generally observed when this treatment is intro duced and continues with long-term administration [8,9]. In contrast, this 1-year study confirms the beneficial effect of tertatolol on renal function previously observed in experimental [17,18] and short-term studies [19][20][21], Particularly, in keeping with what was reported by Ardaillou [20], the decrease in plasma creatinine level is greater the greater the initial level is. and reaches almost 20% in the upper-range subgroup.…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, a renal function impair ment is generally observed when this treatment is intro duced and continues with long-term administration [8,9]. In contrast, this 1-year study confirms the beneficial effect of tertatolol on renal function previously observed in experimental [17,18] and short-term studies [19][20][21], Particularly, in keeping with what was reported by Ardaillou [20], the decrease in plasma creatinine level is greater the greater the initial level is. and reaches almost 20% in the upper-range subgroup.…”
Section: Discussionsupporting
confidence: 87%
“…Tertatolol is a new ß-blocking drug of interest in anti hypertensive therapy as regards its renal hemodynamic effects with preservation or increase in renal blood flow and glomerular filtration rate [11] and its lack of adverse effects on biochemical risk factors for atherosclerosis [12]. The results of phase 1 and II studies which have led to the recommendation of a 5-mg dose of tertatolol once daily will be reviewed in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the vasodilation is more effective in the presence of an ini tial background of renal vasoconstriction, as can be observed in sustained essential hypertension, thus result ing in an absolute increase in renal plasma flow. In addi tion, the increase in glomerular filtration rate observed simultaneously with enhanced renal plasma How sug gests that the vasodilation caused by tertatolol is mainly located on the afferent side of the glomerular arterioles [23].…”
Section: Redistribution O F Vascular Resistancementioning
confidence: 83%
“…Following acute administration, the preserved renal plasma flow observed with tertatolol appears to be the consequence of a lack of vasoconstric tion within the kidney; this takes place in the context of a systemic vasoconstriction [20][21][22]. Following chronic administration, the preserved or increased renal plasma flow appears to be the consequence of renal vasodilation, this takes place in the context of the long-term adapta tion of vascular resistance [20][21][22][23]. Furthermore, the vasodilation is more effective in the presence of an ini tial background of renal vasoconstriction, as can be observed in sustained essential hypertension, thus result ing in an absolute increase in renal plasma flow.…”
Section: Redistribution O F Vascular Resistancementioning
confidence: 99%